2020
DOI: 10.12659/msm.928702
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Speech Repetition Function and the Arcuate Fasciculus in the Dominant Hemisphere Detected by Diffusion Tensor Imaging Tractography in Stroke Patients with Aphasia

Abstract: Background Repetition disorder can be used as an important criterion for aphasia classification, and damaged arcuate fasciculus in the dominate hemisphere has been reported to be closely related to repetition disorder, but the underlying neurological mechanism remains unclear. Material/Methods Fifteen stroke patients with poststroke aphasia and 9 healthy controls were included in the study. The value of fractional anisotropy (FA) in the dominate arcuate fasciculus in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…The recovery is obvious in the acute phase and slows in the chronic phase [ 31 ]. However, studies have shown that the recovery effect of language rehabilitation treatment in the acute stage of motor aphasia after stroke is almost twice that of natural recovery [ 32 ]. Lee J. K. [ 33 ] used resting-state functional connectivity to evaluate the effect of naming in the treatment of poststroke motor aphasia.…”
Section: Research Progress Of Rs-fmrimentioning
confidence: 99%
“…The recovery is obvious in the acute phase and slows in the chronic phase [ 31 ]. However, studies have shown that the recovery effect of language rehabilitation treatment in the acute stage of motor aphasia after stroke is almost twice that of natural recovery [ 32 ]. Lee J. K. [ 33 ] used resting-state functional connectivity to evaluate the effect of naming in the treatment of poststroke motor aphasia.…”
Section: Research Progress Of Rs-fmrimentioning
confidence: 99%
“…Previous studies using brain mapping techniques, have reported that a patient's language ability, such as speech rate, informativeness, efficiency, fluency and naming ability, could be predicted at the chronic stage by the lesion load (a variable combining LV and lesion site) of the AF in the domi-nant hemisphere [42][43][44][45]. Moreover, several diffusion tensor tractography-based studies have demonstrated that language ability is related to the injury severity of the AF in the dominant hemisphere in stroke patients [20][21][22][23][24]. Breier et al [20] have reported that speech-repetition ability was associated with the FA value of the AF in the dominant hemisphere in stroke (hemorrhage and ischemia) patients at the chronic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Tak et al [22] demonstrated that the AQ value was positively correlated with the TV value of the AF in the dominant hemisphere in chronic stroke patients and was higher if the integrity of the AF in the dominant hemisphere was preserved. Wang et al [23] reported that speech-repetition disability within six months of onset was related to a low FA value for the AF in the dominant hemisphere in stroke (hemorrhage and ischemia) patients. Subsequently, Noh et al [2021] reported that the AQ value and an AQ subset score (naming) were positively correlated with the FA value of the AF in the dominant hemisphere and the AQ subset scores for fluency, repetition and naming were negatively correlated with LV in stroke (hemorrhage and ischemia) patients at the early stage (within two months of onset) [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,12,13] Many DTT studies report on injury of the AF and CBT in various brain pathologies. [9,[12][13][14] However, only a few DTT studies report on recovery of an injured AF in patients with brain injury, and no study reported recovery of an injured CBT. [5,8,15] In the current study, we report on a patient whose injured AF and CBT recovered following an infarct in the middle cerebral artery (MCA) territory, demonstrated on serial DTTs.…”
Section: Introductionmentioning
confidence: 99%